Mechanical properties and the microstructure of the plasma-sprayed ZrO2Y2O3 / ZrO2Y2O3CoNiCrAlY / CoNiCrAlY coating - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2016)
ZrO2 stabilized with Y2O3 has superior and excellent physical properties compared to other modern ceramic materials. Due to its high biocompatibility, ZrO2 ceramics in the ZrO2 - Y2O3 system is widely used as a biomaterial in orthopedic surgery. ZrO2 - Y2O3 ceramics is widely applied in the production of the head of the hip, knee prosthesis, temporary holders, and more. ZrO2 is used for a total hip replacement (THR), for an artificial knee joint as well as for the application and development of other medical devices. In order to use ZrO2Y2O3 ceramics (YSZ) in biomedical substrates, it is necessary to deposit coating layers without defects. For the purpose of the deposition of a ZrO28wt.%Y2O3 ceramic coating with the best structural properties, the ZrO2Y2O3 / ZrO2Y2O3CoNiCrAlY / CoNiCrAlY coating system was tested. For financial reasons, the deposition was performed on a steel substrate by applying a CoNiCrAlY bond coating, which does not affect the structure and functionality of the ZrO2Y2O3 ceramic layer. The structure of the layers was tested by the method of light microscopy, and the surface of the upper ZrO28wt.%Y2O3 ceramic coating was tested by the method of scanning electron microscopy (SEM). The obtained characteristics showed that the porosity content in the ceramic layer was not high and that micropores were uniformly distributed. The mechanical properties of the layers were assessed by testing microhardness using the method HV0.3 and tensile bond strength using tensile testing. The values of the microhardness of the ZrO28wt.%Y2O3 coating were satisfactory as well as the tensile bond strength of the coating system.
Keywords: ZrO2; Y2O3; property; microstructures; mechanical properties; layers; Coatings; ceramics; Bonding